Ancient Mesopotamian religion and mythology - Lambert, Wilfred George, 1926-2011. (Tübingen)
xvi, 279 sayfa, [2] sayfa resim
Keywords: “The late W.G. Lambert (1926–2011) was one of the foremost Assyriologists of the latter part of the twentieth century. His principle legacy is a large number of superb critical editions of Babylonian literary compositions. Many of the texts he edited were on religious and mythological subjects. He will always be remembered as the editor of the Babylonian Job (Ludlul bel nemeqi, also known as the Poem of the Righteous Sufferer), the Babylonian Flood Story (Atra-hasis) and the Babylonian Creation Epic (Enuma elish). Decades of deep engagement with these and other ancient Mesopotamian texts gave direction to much of his research and led him to acquire a deep knowledge of ancient Mesopotamian religion and mythology. The present book is a collection of twenty-three essays published by the scholar between the years 1958 and 2004. These endure not only as the legacy of one of the greatest authorities in this specialist field, but also because each makes statements of considerable validity and importance. As such, many are milestones in the fields of Mesopotamian religion and mythology“ --